Stunning method in broiler chickens meat processing - Pinto, Marcos Franke [UNESP]; Bitencourt, Diego A. [UNESP]; Kepczynski, Fernanda [UNESP]; Garcia Neto, Manoel [UNESP]; Ponsano, Elisa Helena Giglio [UNESP] (My University, 2011)
Quality is a variable concept, which involves many factors, depending on the consumer market. In meat production, the concern with environmental aspects, animal welfare and the health and safety of workers is increasing. This work studied the effect of controlled atmosphere stunning of broilers on meat features and biochemical parameters for stress. Cobb broilers were stunned by electrical stunning and by controlled atmosphere with 70% CO2 and 70% CO2 + 30% Argon. After stunning, serum levels of glucose, lactate and corticosterone were compared with those of broilers at rest, immediately before transportation and slaughter and after 12 h of feed withdrawal (control group). At slaughter, blood volume drained during bleeding was not different for the stunning methods tested, ranging from 3.3 to 3.4% birds weight. This finding was important to demonstrate that gas stunning was not responsible for the animals′ death. Final pH in breast (6.1 to 6.2) and thigh (6.3 to 6.5) also did not vary among the different stunning methods (P > 0.05). Lightness (L = 60.55) and redness (a = +8.94) values found for breasts from electrical stunning showed that they were darker and redder (P < 0.05), probably due to changes in blood pressure. Glucose and corticosterone levels were not different between gas stunned birds (302.45 to 315.7 mg/dl and 55.71 to 72.49 ng/ml respectively) and birds at rest (305.95 mg/dl and 50.65 ng/ml) (P > 0.05). These stress indicators were higher (337.65 mg/dl for glucose and 104.13 ng/ml for costicosterone) when electrical stunning was used (P < 0.05). Lactate concentrations were lower (5.4 mmol/l) for birds at rest (P < 0.05) but not different for all stunning methods tested (7.3 to 8.1 mmol/l; P > 0.05). These results show that serum glucose may be used as a stress indicator in birds, with the advantage of being a quick and cheap biochemical test. Gas stunning favored birds′ management during slaughter and so reduced workers′ effort and injury hazard and the amount of feces and dust in the room. To make this method available for a large scale process, adjustments in equipments will be necessary to avoid delays in the processing line.
Keywords: Gas; Controlled atmosphere; Animal welfare; CO2; Electrical